A cobalt metal‐organic framework with small pore size for adsorptive separation of CO2 over N2 and CH4. Issue 10 (18th May 2017) - Shan, Bohan; Yu, Jiuhao; Armstrong, Mitchell R.; Wang, Dingke; Mu, Bin; Cheng, Zhenfei; Liu, Jichang
Abstract : In this study, a new cobalt‐based metal‐organic framework (MOF), [ Co 6 II (μ3 ‐OH)2 (ipa)5 (C3 O2 )(DMF)2 ] (CoIPA) was synthesized. The crystal structure analysis shows that CoIPA is constructed by Co6 (μ3 ‐OH)2 units linked by isophthalic acid forming a sxb topology and it possesses a small pore size of about 4 Å. The new MOF has been characterized using multiple experimental methods. Monte Carlo and Molecular Dynamic simulations were employed to investigate adsorption equilibrium and kinetics in terms of capacity and diffusivity of CO2, N2, and CH4 on CoIPA. The gas adsorption isotherms collected experimentally were used to verify the simulation results. The activated CoIPA sample exhibits great gas separation ability at ambient conditions for CO2 /N2 and CO2 /CH4 with selectivity of around 61.4 and 11.7, respectively. The calculated self‐diffusion coefficients show a strong direction dependent diffusion behavior of target molecules. This high adsorption selectivity for both CO2 /N2 and CO2 /CH4 makes CoIPA a potential candidate for adsorptive CO2 separation. © 2017 American Institute of Chemical Engineers AIChE J, 63: 4532–4540, 2017